Quality changes of refined‐bleached‐deodorized (RBD) palm olein, soybean oil and their blends during deep‐fat frying - Che Man, Y. B.; Liu, J.L.; B., Jamilah; Abdul Rahman, R. (Wiley, 1999)
The quality changes of refined, bleached and deodorized palm olein (RBDPO) and soybean oil (SBO) and their blends were investigated in this study. The oils were studied during intermittent frying of potato chips at 180PT5C for 5 h per day for 5 consecutive days. The indices used for assessment of changes in quality of the oils were fatty acid composition (FAC), peroxide value (PV), anisidine value (AnV), % free fatty acid (FFA), iodine value (IV), % polar component, polymer content, color, viscosity, smoke point and foaming tendency. The results showed that RBDPO was superior to SBO in frying performance in terms of resistance to oxidation, changes in IV, AnV, foaming tendency, % polar component and polymer content. However, SBO performed better than RBDPO with respect to color, viscosity, FAA content and smoke point. Sensory evaluation showed that potato chips fried in both RBDPO and SBO were equally acceptable by the panelists.